2015
DOI: 10.5534/wjmh.2015.33.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Treatment Guidelines for Postpubertal Cryptorchidism

Abstract: Cryptorchidism is a well-known congenital anomaly in children. However, its diagnosis is often delayed for reasons including patient unawareness or denial of abnormal findings in the testis. Moreover, it has been difficult to establish an optimal treatment strategy for postpubertal cryptorchidism, given the small number of patients. Unlike cryptorchidism in children, postpubertal cryptorchidism is associated with an increased probability of neoplasms, which has led orchiectomy to be the recommended treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Even though the testicular volume increased as increasing age, the stiffness was not correlated with age in the CGN group. Previous studies also demonstrated that the UDTs could affect contralateral descended testes, causing pathological changes and increased risk of malignancy than normal testes [27,28]. Our results support the difference of the contralateral descended testes showing lack of normal elasticity change.…”
Section: Discussionsupporting
confidence: 82%
“…Even though the testicular volume increased as increasing age, the stiffness was not correlated with age in the CGN group. Previous studies also demonstrated that the UDTs could affect contralateral descended testes, causing pathological changes and increased risk of malignancy than normal testes [27,28]. Our results support the difference of the contralateral descended testes showing lack of normal elasticity change.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, two separate studies by Shin et al [24] and Lin et al [25] reported cases which demonstrated commencement of spermatogenesis resulting in pregnancy, after late surgical correction of UDT. In a review article, Chung et al [29] made a case for testicular preservation in patients who still desire parenthood, but also the elderly, where there is no further risk of malignancy. In his conclusion, he proposed guidelines for this specific group of patients which is similar to what OH et al proposed, with the added recommendation: in post-pubertal patients with a non-palpable UDT, laparoscopic orchidectomy is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…If the testes are palpable in the groin then the patient needs to be told about their increased risk of testicular cancer, which is approximately 1.7%. 14 There is a 74% increased risk of cancer in the contralateral testes, with approximately a six times increased risk in the ipsilateral testis. If the undescended testis is unilateral this will have almost no effect on fertility, but bilateral cryptorchidism may lead to a marked change in characteristics seen on testicular biopsy and semen paramenters.…”
Section: Varicocelementioning
confidence: 99%
“…It is essential that patients are warned that if the testis cannot be safely mobilised on its blood supply then it will be removed. 14 If a testis is impalpable in an adolescent/adult then it is important to gain as much history and documentation as possible. It is not uncommon to find (but not safe to assume) that a testis has been removed, but it is important not to ignore an unrecognised intraabdominal testis.…”
Section: Varicocelementioning
confidence: 99%
See 1 more Smart Citation